Assessing the epidemiology and seasonality of influenza among children under two hospitalized in Amman, Jordan, 2010‐2013. Issue 2 (11th November 2020) - Rolsma, Stephanie L.; Rankin, Danielle A.; Haddadin, Zaid; Hamdan, Lubna; Rahman, Herdi K.; Faouri, Samir; Shehabi, Asem; Williams, John V.; Khuri‐Bulos, Najwa; Halasa, Natasha B.
Abstract: Background: The disease burden of influenza‐associated hospitalizations among children in Jordan is not well established. We aimed to characterize hospitalizations attributed to influenza in a pediatric population. Methods: We conducted a cross‐sectional study from our viral surveillance cohort in children under 2 years hospitalized with acute respiratory symptoms and/or fever from March 2010 to March 2013. We collected demographic and clinical characteristics, and calculated the frequency of children who met the severe acute respiratory illness (SARI) criteria. Nasal specimens were tested using real‐time reverse transcriptase polymerase chain reaction to detect influenza A, B, or C. Further subtyping for influenza A‐positive isolates was conducted. Results: Of the 3168 children enrolled in our study, 119 (4%) were influenza‐positive. Influenza types and subtypes varied by season but were predominantly detected between December and February. Codetection of multiple respiratory pathogens was identified in 58% of children with the majority occurring among those <6 months. Bronchopneumonia and rule‐out sepsis were the most common admission diagnoses, with influenza A accounting for over 2/3 of children with a rule‐out sepsis admission status. One‐third of children under 6 months compared to 3/4 of children 6‐23 months met the SARI criteria. Conclusions: Influenza was an important cause of acute respiratory illness in children under 2 years. Children <6 months had the highest burden of influenza‐associated hospitalizations and were less likely to meet the SARI global surveillance case definition. Additional surveillance is needed in the Middle East to determine the true influenza burden on a global scale.